Analisis Yuridis Terhadap Efektivitas Regulasi Perlindungan Hak Aksesbilitas Penyandang Disabilitas Di Transportasi Kereta Api Indonesia - Maharani, Dian Sasmitha Dwi; Sutrisno (Lex Stricta : Jurnal Ilmu Hukum, 2025)
Indonesia's diverse geographic conditions demand the provision of appropriate transportation infrastructure. Its primary function is to ensure ease of access and optimize mobility for people and goods, using means such as airplanes, ships, buses, cars, motorcycles, and others. However, in practice, transportation accessibility still faces unique challenges, particularly for passengers with disabilities. The research method used is a normative juridical approach with a legislative approach through an analysis of regulations governing the rights of persons with disabilities, namely Law No. 8 of 2016 and Law No. 23 of 2007 concerning railways. The results of the study indicate that legally, the legal basis for guaranteeing accessibility rights is quite strong, but its implementation is still far from optimal. The implementation of applicable regulations is not fully aligned with the reality on the ground. These problems include the uneven distribution of disability-friendly facilities across all stations, the lack of training for railway personnel, and the absence of an effective oversight mechanism. Therefore, increased synergy between the government and relevant parties is needed to oversee the consistent implementation of regulations.